Study on the Role of the Common House Fly, Musca domestica, in the Spread of ORF Virus (Poxviridae) DNA under Laboratory Conditions - Donato Antonio Raele (MDPI AG, 2021)
ORF virus (Poxviridae) is the causative agent of contagious ecthyma (soremouth), a disease primarily affecting sheep and goats worldwide, but also humans exposed to disease-ridden animals. Pathogens are shed with scabs, and infection mainly occurs by direct contact. Although the disease is relatively benign and self-limiting, the morbidity rate is high in livestock with subsequent significant financial and economic impact. The aim of the study was to experimentally investigate the potential for the housefly, Musca domestica, to act as a mechanical vector of the virus. Homogenate of crusted scabs from ORFV-positive sheep (Italy, Apulia) were used to infect laboratory-reared flies. Flies walking on viral mixture and flies inoculated on their wings were individually placed in Falcon tubes and the ORFV DNA was searched by PCR on tube walls; flies were fed on the same homogenized crusts and their crop and spots (vomit and feces) molecularly examined for ORF DNA at 2, 4, and 6 h. All of the flies (100%) used in the experiments were able to pick up and transmit the viral genome to contact surfaces; 60% were found ORF virus (DNA)-positive in both spots and crop. These results suggest that M. domestica could play a role as potential mechanical vector and/or reservoir in the epidemiology of the ORF virus infection. Thus, house fly management should be considered in the measures to control the disease in ovine–caprine farms.